Lay Participation in Taiwan: Observations from Mock Trials. Issue 1 (30th April 2019) - CHIN, Mong-Hwa
Abstract: This article introduces the designs and the potential problems of the new lay judge system in Taiwan. This article first describes the background of the development of lay participation in Taiwan, and the 2012 Observer Jury System and the 2018 Lay Judge System drafted by the judiciary. The core of this paper is a qualitative study of four mock trials conducted by four district courts in Taiwan. Through observations and interviews with mock trial lay judges, this article addresses three main problems of the new system, including professional judges' domination in deliberations, the comprehensibility of law, and lack of evidence rules. It also provides a discussion of the possible solutions to the problems observed. This article urges that training sessions should be provided to both lay judges and legal professionals, adjust the discovery rule, provide guidance on sentencing, and create evidentiary rules.